The Impact of Perfectionism, Self-Efficacy, Academic Stress, and Workload on Academic Fatigue and Learning Achievement: Indonesian Perspectives - Hendra Robi; Habibi Akhmad; Ridwan Ahmad; Sembiring Dian Arisandy Eka Putra; Wijaya Tommy Tanu; Denmar Denny; Widana I Wayan (Open Education Studies)
The current study examines and evaluates the direct influence of perfectionism, self-efficacy, academic stress, and workload on students’ learning outcomes. The study applied a quantitative survey approach. We implemented a survey as the data collection method. A sample size of 218 students was determined using *G-power to determine the sample size. The data collection technique involved distributing and collecting questionnaires through Google Forms. Quantitative data analysis was performed using the partial least squares-structural equation model method. The results indicate that a relationship between perfectionism and academic fatigue emerged, as well as perfectionism and academic achievement. Self-efficacy is a robust positive determinant of academic fatigue, while academic stress is an affecting factor of academic fatigue. The relationship between workload and academic fatigue appeared significant. Workload and academic achievement are also correlated. Finally, academic fatigue significantly affects academic achievement. Self-efficacy and coping strategies are two main factors influencing learning outcomes.